The effect of deproteinization methods on the properties of glucosamine hydrochloride from shells of white leg shrimp (Litopenaeus vannamei) and black tiger shrimp (Penaeus monodon) - Minh,Thuy Le Thi (2022)
ABSTRACT: The effect of methods to remove protein content on the properties of glucosamine hydrochloride from the shells of white leg shrimp (Litopenaeus vannamei) and black tiger shrimp (Penaeus monodon) was investigated. Chitin from shrimp shells was obtained by demineralization in 6% HCl for 12h, deproteinization by two different methods (first group soaked in 8% NaOH for 36h and second group treated in Alcalase enzyme at the concentration of 0.2% for 36h). Two group samples were converted to glucosamine hydrochloride by soaking in 36.76% HCl solution for 5h at 85 °C. The results of fourier transform infrared spectroscopy (FTIR), solubility and recovery yield analysis showed that deproteinization methods did not significantly affect the properties of glucosamine hydrochloride. However, glucosamine hydrochloride from white leg shrimp shells contained higher recovery yield and solubility than black tiger shrimp shells.